2018
DOI: 10.1590/1679-78254900
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Properties of High Volume Fly Ash Nanosilica (HVFANS) Concrete Subjected to Combined Effect of High Strain Rate and Temperature

Abstract: The study aims to determine the dynamic properties of high volume fly ash nanosilica HVFANS concrete exposed to strain rates between 30.12 to 101.42 s-1 and temperatures of 25, 400, and 700 o C by using split Hopkinson pressure bar SHPB machine. The static and dynamic compressive strengths of HVFANS concrete were slightly lower than plain concrete PC at room temperature, while its values were higher at 400 and 700 o C. The results proved that the CEB model of dynamic increase factor is more reliable to estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Strain rate sensitivity was defined for the concrete and rebar by using dynamic increase factor (DIF) curves, as shown in Figure 2. The DIF curve was obtained during a laboratory test conducted in UKM University on concrete with a compressive strength of 61.18 MPa via the split Hopkinson pressure bar (SHPB) impact test within a strain rate range of up to 103.87 s -1 [37] . For steel, the DIF of grade 60 rebar was determined by using Malvar's equation [38].…”
Section: Geometry Details and Meshingmentioning
confidence: 99%
“…Strain rate sensitivity was defined for the concrete and rebar by using dynamic increase factor (DIF) curves, as shown in Figure 2. The DIF curve was obtained during a laboratory test conducted in UKM University on concrete with a compressive strength of 61.18 MPa via the split Hopkinson pressure bar (SHPB) impact test within a strain rate range of up to 103.87 s -1 [37] . For steel, the DIF of grade 60 rebar was determined by using Malvar's equation [38].…”
Section: Geometry Details and Meshingmentioning
confidence: 99%
“…Mussa et al [27] studied concrete dynamic and static properties using Ns and high-volume fly ash subjected to elevated temperatures of 400°C and 700°C for a fire duration of 2 hours. And found that at 700°C, both concrete mixtures showed a significant decrease in compressive strength; however, the concrete using Ns and high-volume fly ash showed a higher residual strength of 85.13%, compared to the control concrete.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The voltage signals were converted into digital data that can be saved into a computer and analysed via MATLAB software by using a data logger (OMB-DAQ-3000). All the recorded pulses were used to calculate the stress ( ), strain rate (t), and strain ( ), respectively, according to the following equations [47,[52][53][54]: Quarterly connected strain gauges (SGD-3/350-LY11) were utilised to record the elongation of incident and transmitter bars during the test. These gauges were connected to bridge sensors model (OM2-163) to amplify the voltage change.…”
Section: Recorded Signals Of Dynamic Testmentioning
confidence: 99%
“…All the recorded pulses were used to calculate the stress σ(t), strain rate . ε(t), and strain ε(t), respectively, according to the following equations [47,[52][53][54]:…”
Section: Recorded Signals Of Dynamic Testmentioning
confidence: 99%